Decision analysis for the determination of biomass in the territory Tuscia Romana by geographic information system and forest management plans - A. Colantoni (Journal of Agricultural Engineering, 2013)
The growing interest in the development of chains for the use of agroforestry biomass for energy demand, is due to the awareness they are a crucial element to mitigate the global climatic change effects. The true effort is to have a reliable estimation of biomass availability by some instruments like forest management plans, which allow to locate the forest supply and to know the forest biomass availability in a medium period. In this paper we carried out a decision analysis by geographic information system, in Tuscia Romana area comprising 11 municipalities for a total amount of 813 km2. An estimation was carried out taking into account the bibliographic data on the analyzed species, reporting the biomass in weight taken out by the forest cut utilization. A comparison was also performed in field on chestnut trees cut in a sampling area near Bracciano and in a close sawmill. The results show long, medium and short-term dynamics, but some critical points were found related to the process of estimation and to the real procurement of biomass in some years. The results suggest to be care in a possible project of a biomass plant.